Hegemoni dan Ekonomi Politik Dana Keistimewaan di Daerah Istimewa Yogyakarta [Hegemony and Political Economy of Privileged Fund in Special Region of Yogyakarta] - Anggalih Bayu Muh Kamim (Jurnal Politica, 2021)
The Privileged Fund is used to financing five affairs, namely, spatial planning, land, culture, institutions and procedures for filling the positions with governor and vice governor. Various problems such as low participation, institutional problems and the interests of local authorities were identified as the cause of the Privileged Fund not being able to increase welfare. This study looks at the hegemonic perspective to show the consolidation of the ruling class since the promulgation of the Privileged Law until its implementation has an impact on the inability of the community to control the Privileged Fund. This study is a qualitative research with a case study approach. Data was collected through documentation techniques, in-depth interviews and Focus Group Discussions. Data analysis was carried out starting from extracting the problem to drawing conclusions. The results of the study show that the mass action that emerged in support of the Privileged Law did not originate from the aspirations of the citizens, but rather a form of the success of the local ruling class in strengthening the social base. The hegemony of the ruling class plays important roles in preventing the growth of critical awareness from the grassroots community and inhibits organic intellectuals from overseeing the Privileged Fund. Organic intellectuals have not been able to build alternative education and build movement alliances. The ruling class is able to mobilize resources and government structures to keep up its hegemony in the use of the Privileged Fund in the Special Region of Yogyakarta.AbstrakDana Keistimewaan digunakan untuk membiayai lima urusan yakni, tata ruang, pertanahan, kebudayaan, kelembagaan dan tata cara pengisian jabatan gubernur dan wakil gubernur. Berbagai permasalahan seperti rendahnya partisipasi, masalah institusional dan kepentingan pennguasa lokal teridentifikasi menjadi penyebab Dana Keistitmewaan belum mampu membawa peningkatan kesejahteraan. Kajian ini melihat dengan perspektif hegemoni untuk menunjukan konsolidasi kelas penguasa sejak pengusulan Undang-Undang Keistimewaan sampai pelaksanaannya berdampak pada ketidakmampuan masyarakat mengawal pemanfaatan Dana Keistimewaan. Kajian ini adalah penelitian kualitatif dengan pendekatan studi kasus. Pengumpulan data dilakukan melalui teknik dokumentasi, wawancara mendalam dan Focus Group Discussion. Analisis data dilakukan mulai dari penggalian masalah sampai dengan penarikan kesimpulan. Hasil kajian menunjukan aksi massa yang muncul dalam mendukung Undang-Undang Keistimewaan bukanlah berasal dari aspirasi warga, melainkan bentuk keberhasilan kelas penguasa lokal dalam memperkuat basis sosial. Hegemoni kelas penguasa berperan erat dalam mencegah tumbuhnya kesadaran kritis dari masyarakat di akar rumput dan menghambat intelektual organik dalam mengawal penggunaan Dana Keistimewaan. Para intelektual organik belum mampu membangun pendidikan alternatif dan membangun aliansi gerakan. Kelas penguasa mampu memobilisasi sumber daya dan struktur pemerintahan untuk mempertahankan hegemoninya dalam pemanfaatan Dana Keistimewaan di Daerah Istimewa Yogyakarta.